The filament forming reactions of vimentin tetramers studied in a serial-inlet microflow device by small angle x-ray scattering - Saldanha, Oliva (Biomicrofluidics, 2016)
The structural organization of metazoan cells and their shape are established through the coordinated interaction of a composite network consisting of three individual filament systems, collectively termed the cytoskeleton. Specifically, microtubules and actin filaments, which assemble from monomeric globular proteins, provide polar structures that serve motor proteins as tracks. In contrast, intermediate filaments (IFs) assemble from highly charged, extended coiled coils in a hierarchical assembly mechanism of lateral and longitudinal interaction steps into non-polar structures. IF proteins are expressed in a distinctly tissue-specific way and thereby serve to generate the precise plasticity of the respective cells and tissues. Accordingly, in the cell, numerous parameters such as pH and salt concentration are adjusted such that the generation of functional networks is ensured. Here, we transfer the problem for the mesenchymal IF protein vimentin to an in vitro setting and combine small angle x-ray scattering with microfluidics and finite element method simulations. Our approach is adapted to resolve the early assembly steps, which take place in the sub-second to second range. In particular, we reveal the influence of ion species and concentrations on the assembly. By tuning the flow rates and thus concentration profiles, we find a minimal critical salt concentration for the initiation of the assembly. Furthermore, our analysis of the surface sensitive Porod regime in the x-ray data reveals that the formation of first assembly intermediates, so-called unit length filaments, is not a one-step reaction but consists of distinct consecutive lateral association steps followed by radial compaction as well as smoothening of the surface of the full-width filament.